Pola Morbiditas Penyakit Tropis Pada Balita di Wilayah Pesisir Kota Kendari - Irma, Irma; Harleli, Harleli (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The morbidity rate is an important health problem, especially for toddlers because illness is most often found in the early childhood group where at that age toddlers are very susceptible to disease. This study aims to describe the pattern of tropical disease morbidity in children under five in the form of prevalence based on age and sex. This research is an observational survey research with a cross sectional study approach. The population in this study were all children under five in the coastal area of ​​Kendari City with a sample of 160 people who were taken using a combination of non-random and random methods. Data collection was carried out using questionnaires and observation sheets according to complaints and symptoms of illness experienced by toddlers. The results showed that the toddlers who experienced the most exposure to tropical diseases were aged 25-36 months, namely 22 toddlers (25%) and the age group that experienced the least exposure to tropical diseases was 0-12 months of age, which was 2 people (2.5 %), according to gender, most of them are 35 people (60.34%) are women and a small part are 23 people (39.66%) and ARI is a tropical disease infection that mostly occurs in toddlers in coastal areas. The age group of 1-3 years is the age group that most often experiences tropical disease infections with female sex. ARI is a tropical disease that most often occurs in toddlers in the coastal area of ​​Kendari City.